METODE PEMBELAJARAN MEMBACA DAN MENULIS PERMULAAN DI SD SWASTA MUHAMMADIYAH 2 PADANGSIDIMPUAN - Elsi Anni Nora Dalimunthe (DIRASATUL IBTIDAIYAH, 2021)
AbstractReading writing early is a stage of the learning process for early grade elementary school students. Students learn to gain skills and master reading and writing techniques and capture the content of reading well. Therefore teachers need to design the learning of reading writing early well so as to grow the habit of reading as something fun. Scope Of Knowing Reading Writing Beginning 5 stages namely Fantasy Stage (Magical Stage), Self Concept Stage, Image Reading Stage (Bridging Reading Stage), Take-off reader stage, Independet Reader Stage. The implementation of MMP teaching and learning activities is divided into two stages, namely (a) bookless defense, and (b) learning using books. Keywords: Reading, Writing, Beginning